Pedagogical Proposal for Early Childhood Education: A Contemporary Need (Research, Society and Development, 2019)
This experience report aims to discuss the process of elaboration and application of the Pedagogical Political Project (PPP) in Child Education Schools of a municipality in the interior of Rio Grande do Sul, Brazil. This is a qualitative research and had two stages, the first one to begin in 2015, when the said school began the reconstruction of the Political Pedagogical Project and the second in 2017, after the development and application of it. As a result of the research it was inferred that: the integral and collective participation of the protagonists of education, the mobilization of the school community and the commitment of the professional allow the overcoming of the recurring challenges in the (re) construction of the Political-Pedagogical Project, considering the importance, vitality and the guiding conceptions of the work to be developed in the educational institution.